От curriculum vitae к автобиографии: Вальмар Адамс (1899-1993) - Tatiana Shor (Avtobiografija, 2020)
The Estonian poet and essayist, philologist, university teacher Valmar (Vladimir Karl Moritz Alexander) Adams wrote many СVs and autobiographies over his long life. He was born at the turn of the century and was a direct witness to the European turmoil of the twentieth century. His CVs are a unique example of both business and artistic autobiographical genres in completely opposed cultural contexts. He was a citizen of the Russian Empire, of the Estonian Republic and the Estonian SSR, then a citizen of the Reich Commissariat of Ostland within the German Reich, then a citizen of the USSR and again the Republic of Estonia: Adams had to negotiate with his context in his autobiographies at different periods. Iurii Lotman wrote about his colleague: ‘Valmar Adams is a man of versatile giftedness. It is difficult to describe him briefly. I once advised him to write a play where the characters would be the five sides of himself’. In the present article these different sides of Adams are revealed on the basis of documents and autobiographies from the archives of the Literary Museum of Tartu, University of Tartu, and the KGB.